Substitution Between Individual and Source Country Characteristics: Social Capital, Culture, and US Labor Market Outcomes Among Immigrant Women - Francine D. Blau; Lawrence Kahn (Center for Economic Studies and ifo Institute (CESifo), 2015)
Using the New Immigrant Survey, we investigate the impact of immigrant women's own labor supply prior to migrating and female labor supply in their source country on their labor supply and wages in the US. Women migrating from higher female labor supply countries work more in the US. Most of this effect remains after controlling for the women's own labor supply prior to migrating, which itself also strongly positively affects US labor supply. We further find a significantly negative interaction between pre-migration labor supply and source country female labor supply. We obtain similar effects on hourly earnings among the employed.
Keywords: J16; J22; J24; J61; 330; gender; immigration; labor supply; human capital